The Effect of Implementing CTL and PBL Models on Students' Mathematical Problem-Solving Ability - Nevy Wulan Sari; Nizlel Huda; Ade Kumalasari (Riemann: Research of Mathematics and Mathematics Education, 2025)
This experimental research with a quantitative approach will test several learning models on students' mathematical problem solving abilities. The models used are CTL and PBL. This study involved three sample classes including CTL, PBL and Direct Instruction classes. In each learning model, the differences between the three will be examined to see their influence on students' mathematical problem solving abilities. The quantitative analysis used is the Tukey test with a significance level of 0.981. Meanwhile, the direct learning model shows a significance value of 0.024, which means there is no significant influence. Thus, the PBL and CTL learning models have more influence on mathematical problem solving abilities than direct instruction.